Talin and kindlin : batman and robin of Mac1 integrin activation? - Henni Djunaidi. (2009)
Macrophage 1 (Mac1) integrin is a leukocyte-restricted adhesion molecule highly expressed on phagocytes and is essential in the development of immune responses. In a normal physiological condition, activation of Mac1 is initiated via inside-out signaling. The final common step of inside-out signaling is the binding of a cytoplasmic protein talin to the integrin β cytoplasmic tail. Talin-binding unclasps the proximal region of αβ cytoplasmic tails, rendering integrin activation. Recently, another family of cytoplasmic protein kindlin is observed to bind another region along integrin β cytoplasmic tail and cooperate with talin as it boosted up the ligand affinity of platelet integrin and leukocyte function adhesion 1 (LFA-1) integrin upon activation. Thus, this study aims to clarify if kindlin-3 also serves as co-activator of Mac1 in the presence of talin. The findings in 293T transient transfection system suggested that kindlin-3 is likely to serve as the co-activator of Mac1 in the presence of talin because kindlin-3 long (K3L) enhanced the ligand-binding of Mac1 induced by talin head domain (talin-HD), but K3L alone did not activate Mac1. Any possible involvement of kindlin-3 in the cell spreading remains to be further clarified.